1998
DOI: 10.1200/jco.1998.16.11.3556
|View full text |Cite
|
Sign up to set email alerts
|

Full-dose reirradiation for unresectable head and neck carcinoma: experience at the Gustave-Roussy Institute in a series of 169 patients.

Abstract: Full-dose reirradiation combined with chemotherapy was feasible in patients with inoperable HNC. The incidence and severity of late toxicity was markedly increased in comparison to that observed after the first irradiation. Median survival was better than that generally obtained using palliative chemotherapy alone. A small proportion of patients were long-term disease-free survivors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
197
5
10

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 296 publications
(227 citation statements)
references
References 35 publications
15
197
5
10
Order By: Relevance
“…Approximately one fourth of patients included in the current analysis were reirradiated without prior surgery, and 5‐year locoregional control and OS were only 20% and 14%, respectively. Poor outcome for this patient category was also reported by others 18, 19, 22. The dilemma in this situation is that adequate radiation dose for gross disease is often considered not safe and feasible because of the previous radiation treatment.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Approximately one fourth of patients included in the current analysis were reirradiated without prior surgery, and 5‐year locoregional control and OS were only 20% and 14%, respectively. Poor outcome for this patient category was also reported by others 18, 19, 22. The dilemma in this situation is that adequate radiation dose for gross disease is often considered not safe and feasible because of the previous radiation treatment.…”
Section: Discussionsupporting
confidence: 74%
“…Several studies have shown that a longer interval from the last radiotherapy treatment is correlated with an improved survival rate 8, 18. In the current study, in univariate analysis, an improved OS was observed if the time to reirradiation was >3 years (Table 2).…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Palliative chemotherapy is regarded as a standard treatment, but full-dose, repeat irradiation is an option for selected patients and may result in durable control in approximately 10% of such patients (4)(5)(6)(7). However, reirradiation with or without concomitant chemotherapy is associated with a risk for severe organ injury due to a high accumulated radiation dose in up to 80% of the patients and treatment-related death in up to 15% (4)(5)(6)(7)(8). Efficient, well-tolerated treatment options are lacking, and patients with unresectable recurrent head-andneck carcinoma pose a difficult therapeutic problem.…”
Section: Introductionmentioning
confidence: 99%
“…In the prospective RTOG 9610 study and two out of three largest retrospective series (each with [100 patients included), the interval since last RT positively correlated with the survival outcome, with the time cut off point usually identified at 36 months [8,9,11,12]. It appears that with regard to re-treatment interval, the premise should be ''longer is better'', although no impact of delay from first irradiation and opposite observations has been reported in the literature [12][13][14]. This rule probably does not apply if the previous radiation missed the area of recurrence.…”
mentioning
confidence: 99%